2017
DOI: 10.13057/biodiv/d180109
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and utilization of bamboo to support life’s the community of Karangwangi Village, Cidaun Sub-District of Cianjur, Indonesia

Abstract: Abstract. Setiawati T, Mutaqin AZ, Irawan B, An'amillah A, Iskandar J. 2017. Species diversity and utilization of bamboo to support life's the community of Karangwangi Village,. Bamboo is closely related to the lives of Indonesian people, especially in the rural area. Indonesia has a high diversity of bamboo species with multiple social, economic, cultural and ecological functions. Village communities have taken advantage of bamboo as a building material, furniture, handicrafts, household items, food, and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 9 publications
0
23
0
2
Order By: Relevance
“…When utilized properly, this kind of bamboo can, actually, become the living source of the local people because it can be used as the raw material to make handicraft and furniture. Setiawati, Mutaqin, Irawan, An'amillah, and Iskandar (2017) found that flexible nature of buluh belangke makes crafters easily form a wide range of household products industry. Therefore, by using this bamboo in playing cengkah-cengkah game, it gains its popularity back and is expected to be utilized by Karonese people in these two villages as their additional living source.…”
Section: Resultsmentioning
confidence: 99%
“…When utilized properly, this kind of bamboo can, actually, become the living source of the local people because it can be used as the raw material to make handicraft and furniture. Setiawati, Mutaqin, Irawan, An'amillah, and Iskandar (2017) found that flexible nature of buluh belangke makes crafters easily form a wide range of household products industry. Therefore, by using this bamboo in playing cengkah-cengkah game, it gains its popularity back and is expected to be utilized by Karonese people in these two villages as their additional living source.…”
Section: Resultsmentioning
confidence: 99%
“…When utilized properly, this kind of bamboo can, actually, become the living source of the local people because it can be used as the raw material to make handicraft and furniture. Setiawati, Mutaqin, Irawan, An"amillah, and Iskandar (2017) found that flexible nature of Gigantochloaapus makes crafters easily form a wide range of household products industry. Therefore, by using this bamboo in playing cengkah-cengkah game, it gains its popularity back and is expected to be utilized by Karonese people in these two villages as their additional living source.…”
Section: Discussionmentioning
confidence: 99%
“…Plant materials were obtained from in situ collections of Bogor Botanical Garden and also Universitas Padjadjaran Department of Biology bamboo collection from Karawangi. Bamboo species from K was previously classified based on Dransfield and Widjaja (1995) and Widjaja (2001) (Setiawati et al 2017). Total of 25 species from five different bamboo genera was used for analysis.…”
Section: Plant Materialsmentioning
confidence: 99%